Japanese Language Training of Intern Trainees at Vocational Education and Training Centers in Indonesia: Problems and Causes - Widianti, Susi; Putra, Jeni; Hayati, Novia (Makassar State University, 2026)
This study reports on the investigation of problems and causes of lack of Japanese language knowledge and skills of Indonesian intern trainees, as also highlighted in some previous studies, such as by Kamiya (2017), Wu (2020), and Pranasari and Iskandar (2022). Involving 262 Japanese language teachers at 177 vocational education and training centers spread all over Indonesia as the participants, this qualitative study collects the data via Google Form, investigating three key areas, involving teacher, teaching process, and students that are potentially contributing to the problems and causes that result in the lack of Japanese language knowledge and skills of Indonesian intern trainees. The results show that the first and foremost problem that contributes to the lack of Japanese language knowledge and skills of Indonesian intern trainees is the teacher. The main cause is their low education background; apart from not meeting the standards set by the Indonesian government as enacted in the Legislation of the National Education System Number 20 Year 2003 Article 39 Line 2 and the Government Rule Number 19 Year 2005, they have low competencies, particularly in pedagogy and professionalism. Their limited pedagogy and professional literacies, skills, and experiences have contributed to the poor performance of the teaching and learning process and the lack of students’ knowledge and skills in Japanese language education.